1994
DOI: 10.1111/j.1476-5381.1994.tb14050.x
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation by ACE inhibitors of the dilator response to bradykinin in the coronary microcirculation: interaction at the receptor level

Abstract: 1 To examine the possibility that angiotensin-converting enzyme (ACE) inhibitors modulate the action of bradykinin at the receptor level, their effect on the dilator response to bradykinin was studied in the isolated saline-perfused heart of the rabbit. 2 Continuous infusion of bradykinin (10 nM were unable to elicit a significant change in CPP or PGI2 release while ramiprilat and another ACE inhibitor, quinaprilat, were still active in the presence of these substrates. 6 To reveal the potential B2-receptor ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(44 citation statements)
references
References 25 publications
1
42
0
1
Order By: Relevance
“…11,13 However, this effect can be related to a direct resensitizing influence on receptor regulation only if the desensitized receptor will not respond to increasing BK doses, a prerequisite that has not been established in previous studies. In contrast, the present study demonstrated a maintained reactivity to high BK concentrations in the desensitized state that can be interpreted as a stimulation-dependent loss of BK potency.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…11,13 However, this effect can be related to a direct resensitizing influence on receptor regulation only if the desensitized receptor will not respond to increasing BK doses, a prerequisite that has not been established in previous studies. In contrast, the present study demonstrated a maintained reactivity to high BK concentrations in the desensitized state that can be interpreted as a stimulation-dependent loss of BK potency.…”
Section: Discussionmentioning
confidence: 96%
“…11,13 This effect was reproduced in the rat heart, in which the vasodilatory effect of BK (0.2 mol/L) ceased during a 30-minute application (78Ϯ8% loss of vasodilation, half-maximum desensitization after 20Ϯ3 minutes, nϭ5) but was completely restored on subsequent treatment with ramiprilat (250 nmol/L; Figure 3). Consistent with previous studies, 11,13 this resensitization was abolished by the B 2 antagonist icatibant (HOE140, 1 mol/L) administered 2 minutes before ramiprilat (data not shown). The same experiment performed with the stable agonist FR190997 (0.1 mol/L) induced an equivalent course of desensitization, but the subsequent application of ramiprilat was ineffective (Figure 3).…”
Section: Receptor Resensitization and Desensitizationmentioning
confidence: 92%
See 2 more Smart Citations
“…These findings demonstrate that ACEis selectively potentiate the B 2 -receptor-mediated vascular effects of bradykinin independently of their ACE-inhibiting properties, and this might be related to differences in molecular structure. 154,155 ACEis also induce cross-talk between the transmembrane protein ACE and the B 2 -kinin receptor, probably by formation of a heterodimer. This protects high-affinity receptors, blocks receptor desensitization and decreases internalization, thereby potentiating BK beyond blocking its hydrolysis.…”
Section: Looking Beyond Ace Inhibitionmentioning
confidence: 99%